Cerebral Palsy due to Intracranial Hemorrhage Caused by Consumptive Coagulopathy in Protein C Deficiency: A Case Report - 조유나; 박천웅; 박은숙; 최자영; 나동욱; 이영목 (Journal of the korean child neurology society, 2017)
Protein C (PROC) is a potent anticoagulant inactivating coagulation factors Va and VIIIa. PROC deficiency is very rare condition inherited as an autosomal dominant or recessive trait, and associated with various thromboembolic and ischemic conditions. Moreover, severe form of PROC deficiency can cause fatal hemorrhagic complications due to consumptive coagulopathy. We reported two children with hemorrhagic stroke who were diagnosed as severe PROC deficiency caused by two different types of compound heterozygous PROC gene mutations. We described results of laboratory tests, genetic analysis, brain magnetic resonance images, and functional outcomes. Both children received prophylactic anticoagulation therapy and presented with purple-colored skin lesions during rehabilitation. Purpura fulminans caused by insufficient anticoagulation should be differentiated from hematoma caused by excessive anticoagulation therapy in these children. KCI Citation Count: 0